Emerging role of hypothalamus in the metabolic regulation in the offspring of maternal obesity - Zhang, Jingyi; Li, Sujuan; Luo, Xiaoping; Zhang, Cai (Frontiers in Nutrition, 2023)
Maternal obesity has a significant impact on the metabolism of offspring both in childhood and adulthood. The metabolic regulation of offspring is influenced by the intrauterine metabolic programming induced by maternal obesity. Nevertheless, the precise mechanisms remain unclear. The hypothalamus is the primary target of metabolic programming and the principal regulatory center of energy metabolism. Accumulating evidence has indicated the crucial role of hypothalamic regulation in the metabolism of offspring exposed to maternal obesity. This article reviews the development of hypothalamus, the role of the hypothalamic regulations in energy homeostasis, possible mechanisms underlying the developmental programming of energy metabolism in offspring, and the potential therapeutic approaches for preventing metabolic diseases later in life. Lastly, we discuss the challenges and future directions of hypothalamic regulation in the metabolism of children born to obese mothers.